2021
DOI: 10.1101/2021.02.17.431720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phospholipid membrane formation templated by coacervate droplets

Abstract: We report formation of coacervate-supported phospholipid membranes by hydrating a dried lipid film in the presence of coacervate droplets. In contrast to traditional giant lipid vesicles formed by gentle hydration in the absence of coacervates, the coacervate-templated membrane vesicles are more uniform in size, shape, and apparent lamellarity. Due to their fully-coacervate model cytoplasm, these simple artificial cells are macromolecularly crowded and can be easily pre-loaded with high concentrations of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The assembly of phospholipid membrane on coacervates represents a further step to construct synthetic cells with both hallmarks of cell envelope and cytoplasm and may bridge the gap between coacervate-based protocell models and membrane bounded biological cells. Bare coacervates have recently been utilized templates to incubate with lipids in ethanol or hydrated lipid film, resulting in polydisperse giant phospholipid vesicles with apparent lamellarity 37,38 . In this work, through the freeze-thaw treatment of monodisperse coacervates coated by DOPC/DOPS/Chol (37/3/10) liposomes, we demonstrate the first example for the bulk assembly of monodisperse GUVs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly of phospholipid membrane on coacervates represents a further step to construct synthetic cells with both hallmarks of cell envelope and cytoplasm and may bridge the gap between coacervate-based protocell models and membrane bounded biological cells. Bare coacervates have recently been utilized templates to incubate with lipids in ethanol or hydrated lipid film, resulting in polydisperse giant phospholipid vesicles with apparent lamellarity 37,38 . In this work, through the freeze-thaw treatment of monodisperse coacervates coated by DOPC/DOPS/Chol (37/3/10) liposomes, we demonstrate the first example for the bulk assembly of monodisperse GUVs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4b). Recent work indicated that coacervate-supported phospholipid membrane contained defects and thus was leaky 37 . Here, we show that the membrane permeability of coacervate-supported GUVs can be tunable.…”
Section: Resultsmentioning
confidence: 99%
“…However, relevant life-like properties driven by protein networks observed in single compartment LLPS system, such as division, have also been observed (Song et al 2018). Nevertheless, further study of enzymatic cascades or networks could be complemented by recent studies demonstrating a wide range of multiphase membraneless droplet systems (Mountain and Keating 2020Keating , 2021Lu and Spruijt 2020;Sato et al 2020). These systems should be subjects of further study, perhaps even as a mechanism to show prebiotically relevant catalytic ribozyme cascades within a primitive compartment.…”
Section: Biological Processes Imbued Into Llps Systemsmentioning
confidence: 99%
“…Encapsulation or assembly of LLPS systems within liposomes or vesicles could result in the formation of an artificial cell with similarities to membraneless compartment-containing modern cells. For example, various aspects of the structure and function of a number of liposome-encapsulated LLPS systems have been studied (Helfrich et al 2002;Long et al 2005;Li et al 2008;Crowe and Keating 2018;Liu et al 2019;Love et al 2020;Cakmak et al 2021). While these studies share a common goal, they often differ in the construction of each system.…”
Section: Phase Separation In Artificial Cell Researchmentioning
confidence: 99%
See 1 more Smart Citation